Small and medium enterprise trends, themes, and global contributions: bibliometric analysis - Marsanto Adi Nurcahyo (Jurnal Manajemen, 2025)
Small and medium enterprise (SME) performance is critical to economic development, fostering innovation, employment, and sustainability. This study aims to analyze key bibliometric indicators to uncover trends, influential contributors, and thematic developments in SME performance research. Using 7,494 articles indexed in the Scopus database (1988–November 2024), the study reveals a 20.52% annual growth rate in publications. The Journal of Small Business and Enterprise Development emerges as the most productive journal, while Lubatkin et al.'s 2006 work on ambidexterity is the most globally cited. Thematic analysis identifies innovation, sustainability, and strategic management as pivotal themes, with digital transformation and big data analytics gaining prominence in recent years. Collaboration networks highlight significant contributions from the UK, China, and Indonesia, emphasizing global partnerships. This study concludes that SME performance research is dynamic and evolving, with innovation and sustainability at its core, underscoring the need for further exploration into these critical areas.